PENGEMBANGAN MEDIA PERMAINAN MATEMATIKA KARTU CERDAS TANGKAS BILANGAN ROMAWI - Putik Vebimawarti (Universitas Muhammadiyah Purwokerto, 2018)
The aim of this research was to 1) find out the development of the learning media of fast smart cards of cardinal number; 2) find out the feasibility of the development of the learning media of fast smart cards of cardinal number; 3) find out the effectiveness of the learning media of fast smart cards of cardinal number toward the students’ learning achievement in fourth grade elementary school students; 4) find out the teacher’s response toward the learning media development in mathematics teaching-learning process using fast smart cards of cardinal number; and 5) find out the students’ response toward the learning media development in mathematics teaching-learning process using fast smart cards of cardinal number in fourth grade elementary school student. This research is a research and development research. The result of the development was the games media of fast smart cards of a cardinal number that had been tried-out fourth grade SD N Sokaraja Kidul. The result of the media validation showed that the learning media of fast smart cards of a cardinal number was in “valid” criteria. This research used an experimental design of The True Control Group, based on the result of the research. There was an effect on the learning media of fast smart cards of a cardinal number using games toward the students’ learning achievement, and the teacher’s response toward the media tryout was in “agree very much” criteria, while the students’ response toward the media tryout was in “very good” criteria. There were 19 students who all gave a very good response.